The Narrative Treatment of The Climate Change Topic in Film (Al-Academy, 2025)
The high popularity of cinema was not born out of a vacuum, but rather was achieved by the recipient's deep belief that the film is more than an attempt at entertainment. Cinema is the philosophy of the age, which addresses important issues and presents them through its story framed by a specific logic and driven by an influential emotional structure, which prepares the recipient to care about these issues and absorb them. Climate change is one of the most important topics that cinema has begun to adopt in the recent period and present within narrative structures that increase the recipient's awareness of this imminent danger that affects his life today. Based on this importance of the cinematic treatment of the topic of climate change, the researcher identified the topic of this research, which bore the following title (The Narrative Treatment of The Climate Change Topic in Film). The importance of the research emerges in that it addresses an important issue. And then the goal of the research and the limits of the research were presented. Then the researcher moved to the theoretical framework and concluded it with a set of indicators. As for the third chapter, (research procedures), and the researcher identified a deliberate research sample represented by the film (The Day After Tomorrow 2004). A set of results was reached, followed by conclusions, the most important of which are: 1. The core interest of cinematic intellectual construction is to present stories that encompass human issues and the changes that occur in their lives. Therefore, the topic of climate change has entered the narrative structures of cinematic films for nearly six decades, as climate fiction films have discussed the causes and consequences of this phenomenon. 2. Cinema, due to its unique structure, has tremendous potential to influence its audience, which increases their interest in the issues it raises in its stories. Therefore, cinema has contributed to raising public awareness of climate change by presenting it in its films. 3. The film industry has recently begun to adopt production policies that reduce pollution emitted during the various stages of filmmaking. Finally, the research concluded with a list of references.